Public Sector Innovation: An Exploration into the BBC’s History - Azeez NazeerAhamed, Nishanth (2016)
The Governments, around the world are increasingly recognizing the need for innovation in the public sector in response to the major problems such as shortage of resources, natural calamities etc. and are thus trying to understand the factors that can motivate and factors that limit public sector innovation. This dissertation tried to understand the public sector innovation with particular focus on the motivation and barriers majorly among other objectives, taking the case of loudspeaker innovation in the BBC during the post war period. The research method adopted for this study included an extensive literature review and qualitative case study by conducting an historical archival record analysis of the BBC archival records, available in the BBC Written Archives, Caversham. The findings from this study shows that, objective for achieving quality and consistency, along with the issues in supply as the major motivation for loudspeaker innovation, whereas the factors such as devoting time to carry out testing, loss of key capabilities and expertise in the form of employee resignations and disputes formed the barriers to innovation within the British Broadcasting Corporation. It was also found that the Designs department were the reason behind majority of the innovations within the BBC.